Structure, decoration and materials: Mughal Mosques of medieval Dhaka (Journal of the Bangladesh Association of Young Researchers, 2011)
The corrected PDF for this article was loaded on 10/02/2011.Muslim architecture has been initiated from the very beginning of Islamic heritage which is started by the mosque, introduced by Prophet Muhammad (Sm.). From the early age of Islam, Muslim architecture has been developed from the foot point of mosque. Gradually by the expansion of Islam it was circulated in various countries of the world. Later stage, mosque architecture has been introduced into India at the very beginning of 13th century. Mosque architecture in medieval time exposes clearly its sacred identity but in secular architecture, the ideas are not spiritually motivated in cosmic sense. Certainly structural idea, materials and its functionality played a vital role in that era and beyond. Functionality, aesthetic use of materials and technique with effective manner are depending on assimilated technologies. Besides these, integrated process of standard materials, skilled labor, innovative idea and socio-economic as well as geographical factors are important for building any magnificent architecture. Mughal mosques of Dhaka are the unique example of architecture where the ideas and used materials have been effectively amalgamated in the medieval context of Bengal. The present study is an attempt to analyze the structure, structural decoration and use of materials of medieval Mughal Mosques of Dhaka. The study will also cover exclusively interior and exterior structure and design of the mosques. The focus of the study is to demonstrate the effective use of available materials, for representing own belief and cultural exclusivity to the architecture.Keywords: Structure; decoration; materials; medieval Dhaka; Mughal Mosque; Muslim architectureDOI: 10.3329/jbayr.v1i1.6841Journal of Bangladesh Association of Young Researchers Vol.1(1) 2011 pp.93-107